2020
DOI: 10.3390/ijms21155575
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Repair Deficit in Facioscapulohumeral Muscular Dystrophy

Abstract: Deficits in plasma membrane repair have been identified in dysferlinopathy and Duchenne Muscular Dystrophy, and contribute to progressive myopathy. Although Facioscapulohumeral Muscular Dystrophy (FSHD) shares clinicopathological features with these muscular dystrophies, it is unknown if FSHD is characterized by plasma membrane repair deficits. Therefore, we exposed immortalized human FSHD myoblasts, immortalized myoblasts from unaffected siblings, and myofibers from a murine model of FSHD (FLExDUX4) to focal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…Impaired muscle oxygenation in FSHD may also contribute to ROS sensitivity (Olivier et al , 2016 ; Wilson et al , 2018 ). Other molecular mechanisms underlying oxidative stress sensitivity include p21 upregulation (Winokur et al , 2003a ), increased HIF1α (Tsumagari et al , 2011 ; Banerji et al , 2015 ; Banerji et al , 2017 ; Lek et al , 2020 ), mitochondrial dysfunction (Turki et al , 2012 ; Banerji et al , 2019 ), RAGE‐NF‐κB signalling (Macaione et al , 2007 ) and membrane repair deficits (Bittel et al , 2020 ). Compensatory mechanisms for oxidative stress are also enhanced in FSHD, an example being increased catalase to remove H 2 O 2 (Turki et al , 2012 ; Yao et al , 2014 ).…”
Section: Oxidative Stress Sensitivity and The Glutathione Redox Pathwaymentioning
confidence: 99%
“…Impaired muscle oxygenation in FSHD may also contribute to ROS sensitivity (Olivier et al , 2016 ; Wilson et al , 2018 ). Other molecular mechanisms underlying oxidative stress sensitivity include p21 upregulation (Winokur et al , 2003a ), increased HIF1α (Tsumagari et al , 2011 ; Banerji et al , 2015 ; Banerji et al , 2017 ; Lek et al , 2020 ), mitochondrial dysfunction (Turki et al , 2012 ; Banerji et al , 2019 ), RAGE‐NF‐κB signalling (Macaione et al , 2007 ) and membrane repair deficits (Bittel et al , 2020 ). Compensatory mechanisms for oxidative stress are also enhanced in FSHD, an example being increased catalase to remove H 2 O 2 (Turki et al , 2012 ; Yao et al , 2014 ).…”
Section: Oxidative Stress Sensitivity and The Glutathione Redox Pathwaymentioning
confidence: 99%
“…Lipid peroxidation has been found in FSHD patient muscles [42], and there are membrane repair deficits in FSHD myoblasts and DUX4 expressing murine myofibres ex vivo, which are alleviated through antioxidant treatment [71]. Membrane lipid peroxidation is a comparably specific oxidative mechanism and it is unclear how more general oxidative/nitrosative protein modifications affect muscle function in FSHD.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of DUX4-induced oxidative stress as a negative regulator of FSHD myogenesis has mainly been shown in DUX4 overexpression systems, where antioxidants can alleviate myopathic phenotypes [28,44,71], but rarely in FSHD patient-derived cellular models, marked by much lower and sporadic DUX4 expression. In addition, conventional, non-targeted antioxidants have been investigated in all but one study [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on exon 3-targeting gapmers, we saw improvements in muscle cell fusion and size, as well as minimal to no effects on potential off-target genes in vitro. A separate study also found that treatment with one of the 2′-MOE gapmers increased membrane repair in immortalized patient myoblasts (Bittel et al, 2020). One gapmer from each chemistry was also tested in the FLExDUX4 model, which carry a stably integrated, Creinducible DUX4 transgene (Jones and Jones, 2018).…”
Section: Oligonucleotide Therapiesmentioning
confidence: 99%